2014
DOI: 10.4055/cios.2014.6.2.242
|View full text |Cite
|
Sign up to set email alerts
|

A Tenosynovial Giant Cell Tumor Arising from Femoral Attachment of the Anterior Cruciate Ligament

Abstract: The localized type of tenosynovial giant cell tumor usually occurs on the palmar side of fingers and toes. Tenosynovial giant cell tumors of the tendon sheath are rarely intra-articular. We report a giant cell tumor of the tendon sheath arising from femoral attachment of the anterior cruciate ligament and its treatment with arthroscopy in a 28-year-old man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
4
0
2
Order By: Relevance
“…The knee was found to be stable after the excision. 13 In our case to begin with, the diagnostic arthroscopy was performed through anteromedial and anterolateral portals. A posterolateral portal was used to gain better access for complete excision of the tumour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The knee was found to be stable after the excision. 13 In our case to begin with, the diagnostic arthroscopy was performed through anteromedial and anterolateral portals. A posterolateral portal was used to gain better access for complete excision of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Lee at al. 13 reported a case of 29-year-old man affected by an intra-articular localized tenosynovial giant cell tumour of the tendon sheath arising from the ACL. On MRI the mass was situated behind the ACL and was attached near to its femoral attachment.…”
Section: Discussionmentioning
confidence: 99%
“…While due to the high recurrence of diffuse PVNS, finding more effective therapies for PVNS remains a theme of dispute. In a retrospective review of the patients who accepted surgical treatment between 1990 and 2022 [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , the results exhibit that higher recurrence rate of arthroscopic synovectomy compared with open synovectomy, However, the arthroscopic therapy is a minimally aggressive surgical operation that could narrow the scope of operation, lessen tissue trauma, and promote early functional exercise, allowing the earlier return to the daily life [24] . The combined anterior arthroscopic and posterior open synovectomy in the knee could be a good option because some researches have shown that the recurrence rate of it is lower than arthroscopic synovectomy and open synovectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Os TTCG são raros, correspondendo a aproximadamente 1,5% do total de tumores de tecidos moles 1 . São mais frequentemente observados em pacientes com idade entre 30 Brazilian Journal of Development, Curitiba, v.9, n.8, p. 25252-25258, aug., 2023 e 50 anos, com maior prevalência no sexo feminino (2:1) 3,4,5 . Podem acometer qualquer articulação sinovial, incluindo o quadril, tornozelo, ombro e cotovelo e há também registros de forma poli articular em crianças 8,9 .…”
Section: Introductionunclassified